Transcriptome Profiling-Based Analysis of Carbohydrate-Active Enzymes in Aspergillus terreus Involved in Plant Biomass Degradation - Corrêa, Camila L.; Midorikawa, Glaucia E. O.; Filho, Edivaldo Ximenes Ferreira; Noronha, Eliane Ferreira; Alves, Gabriel S. C.; Togawa, Roberto Coiti; Silva-Junior, Orzenil Bonfim; Costa, Marcos Mota do Carmo; Grynberg, Priscila; Miller, Robert N. G. (Frontiers in Bioengineering and Biotechnology, 2020)
Given the global abundance of plant biomass residues, potential exists in biorefinery-based applications with lignocellulolytic fungi. Frequently isolated from agricultural cellulosic materials, Aspergillus terreus is a fungus efficient in secretion of commercial enzymes such as cellulases, xylanases and phytases. In the context of biomass saccharification, lignocellulolytic enzyme secretion was analyzed in a strain of A. terreus following liquid culture with sugarcane bagasse (SB) (1% w/v) and soybean hulls (SH) (1% w/v) as sole carbon source, in comparison to glucose (G) (1% w/v). Analysis of the fungal secretome revealed a maximum of 1.017 UI.mL-1 xylanases after growth in minimal medium with SB, and 1.019 UI.mL-1 after incubation with SH as carbon source. The fungal transcriptome was characterized on SB and SH, with gene expression examined in comparison to equivalent growth on G as carbon source. Over 8000 genes were identified, including numerous encoding enzymes and transcription factors involved in the degradation of the plant cell wall, with significant expression modulation according to carbon source. Eighty-nine carbohydrate-active enzyme (CAZyme)-encoding genes were identified following growth on SB, of which 77 were differentially expressed. These comprised 78% glycoside hydrolases, 8% carbohydrate esterases, 2.5% polysaccharide lyases, and 11.5% auxiliary activities. Analysis of the glycoside hydrolase family revealed significant up-regulation for genes encoding 25 different GH family proteins, with predominance for families GH3, 5, 7, 10 and 43. For SH, from a total of 91 CAZyme-encoding genes, 83 were also significantly up-regulated in comparison to G. These comprised 80% glycoside hydrolases, 7% carbohydrate esterases, 5% polysaccharide lyases, 7% auxiliary activities (AA) and 1% glycosyltransferases. Similarly, within the glycoside hydrolases, significant up-regulation was observed for genes encoding 26 different GH family proteins, with predominance again for families GH3, 5, 10, 31 and 43. A. terreus is a promising species for production of enzymes involved in the degradation of plant biomass. Given that this fungus is also able to produce thermophilic enzymes, this first global analysis of the transcriptome following cultivation on lignocellulosic carbon sources offers considerable potential for the application of candidate genes in biorefinery applications.